ANALYSIS OF THE IMPACT OF COVID-19 ON INCREASING LABOR INCOME IN EAST JAWA - Arisetyawan, Kukuh; Pudjihardjo, M.; Attaqi, Lifya Fillahi; Putri, Natasya Aditya; Maharatni, Rina Dwi (Jurnal Ilmu Ekonomi, 2023)
The Covid-19 pandemic has forced the Government to set a large-scale social restriction policy. This policy impacts all areas of life, including economic growth and employment in East Java, especially income sustainability. This study aimed to identify the influence of sociodemography on the increase in worker income during the Covid-19 period in East Java. The data from this study is secondary data from the results of SAKERNAS 2020 obtained from BPS. The data were analyzed using the Multiple Regression Analysis methods. The results of this study indicate that the dependent variable, Covid, Gender, Age, Working Hours, Work From Home, Internet, Promotion, Formal Sector, and transactions significantly affect workers' income during the pandemic. In contrast, the dependent variable communication does not substantially affect workers' pay during the pandemic.